(untitled) (Research, Society and Development, 2020)
Concomitant with changes in behavior by people with schizophrenia, discriminatory behaviors driven by prejudice are real in today’s society, even after the Psychiatric Reform movement. In this perspective, this study aimed to identify the occurrence of stigma and discrimination phenomena in the daily life of people with schizophrenia. This is a cross-sectional study with a qualitative approach, conducted with 12 people with schizophrenia, with ties in a Psychosocial Care Center in a city in the Midwest of São Paulo State. Data collection took place between December 2018 and February 2019, through interviews with a semi-structured instrument prepared by the authors. Data were subjected to thematic content analysis. All research participants signed the informed consent form. The research was submitted and approved by the Research Ethics Committee. The participants’ self-perception about the experience of discrimination and / or stigma was affirmed by 8 (66.7%) of the participants, and was present in all situations surveyed. Two categories were organized with their thematic units. The categories were: 1 - The experience of prejudice and stigma in the condition of schizophrenia, and 2 - Challenges related to the condition of being schizophrenic. It is observed that stigmatization remains and reigns in society, health professionals and the bearer of the disorder itself, with discrimination directed at people with mental disorders, including schizophrenia. The stigmatizing and discriminatory social behavior addressed to people with schizophrenia is real, aggressive and destructive.